Decent Employment and Poverty Alleviation for Socio-Economic Development and Its Implications for the Well-Being of the Citizenry in South Africa - OLABIYI, OLANIYI JOSHUA (Applied Studies in Agribusiness and Commerce, 2022)
The need for governments and private employers to adequately provide decent work within the economy for all its inhabitants cannot be over-emphasized. This imperative is even more important since most obtainable work have been characterized by many detrimental dimensions which can be considered as constituting ‘indecent employment’. From the viewpoint of human development, the paper examines how ‘decent employment’ can serve as an antidote to poverty. Thus, decent employment can positively affect both material and non-material social development which include health, education, social security, food security and overall well-being.. The present paper is borne out of the desire to empower the average South African citizen in specifically attaining an improved socio-economic living standard.  This paper employs a qualitative, thematic analysis of selected reported cases of perceived ‘indecent’ or non-meaningful employment from both informal and formal sectors’ Additionally, this paper highlights instances in which employees  have experienced  challenges in getting ‘dignified’ or decent employments as a result of  casualization, outsourcing, short-term contracts, and temporary employments. This interpretive, qualitative approach was adopted to put forward a somewhat empirical evidence of the potential beneficial effect of decent employment on human and socio-economic development. The main contribution of this paper is that it foregrounds the need for decent employment of the workforce in addressing the three-pronged societal challenges of unemployment, inequality and poverty. The paper posits that decent employment significantly contributes to national socio-economic development and poverty alleviation or eradication.